Handbook of economic growth - Aghion, Philippe, 1956-; Durlauf, Steven N., 1958- (Handbooks in economics (Elsevier),, 2005)
The Handbook of Economic Growth provides a broad review of the research topics, empirical findings, and methods that comprise modern growth economics. The chapters, written by research leaders, summarize and evaluate recent advances while explaining where further research might be profitable. With analyses that are provocative and controversial because they are so directly relevant to public policy and private decision-making, this volume upholds the standard for excellence in applied economics set by Volumes 1A and 1B (2005).